A Facile One-pot Synthesis of 1-Arylpyrazolo[3,4-d]Pyrimidin- 4-ones - Ping Zhong (Molecules, 2010)
One pot synthesis of 1-arylpyrazolo[3,4-d]pyrimidin-4-ones by the reaction of 5-amino-N-substituted-1H-pyrazole-4-carbonitrile with different lower aliphatic acids in the presence of POCl3has been developed. The structures of all the title compounds have been confirmed by IR, 1H-NMR, 13C-NMR, and elemental analyses. Moreover, the structures of one of these compounds, 2c, was confirmed by single-crystal X-ray diffraction.